Mutual linguistic borrowing between English and Arabic - Alhussami, Ahmed Abdullah (Cambridge Scholars Publishing, 2020)
This book focuses on the lexical borrowing between English and Arabic, and offers historical background regarding the contact between these two languages. It sheds light on why and how both languages have come in contact, showing how the hegemony of the English language can be clearly seen in its impact on Arabic. Simultaneously, the text describes the role that Arabic played in shaping and enriching English in its early phase.